Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
1) x - 2 = -6
x = -6 + 2
x = -4
2) -5 . x - ( -3 ) =13
-5 . x = 13 + ( -3 )
-5 . x = 10
x = 10 : ( -5 )
x = -2
![](https://rs.olm.vn/images/avt/0.png?1311)
1 ) ( x - 1 ) . ( x - 3 ) = 0
=> x - 1 = 0 hoặc x - 3 = 0
=> x = 1 hoặc x = 3
2 ) ( x + 5 ) ( x - 4 ) = 0
=> x + 5 = 0 hoặc x- 4 = 0
=> x = -5 hoặc x = 4
3 ) -12 + ( x - 9 ) = 0
=> x - 9 = 0 - -12
=> x - 9 = 12
=> x = 12 + 9
=> x = 21
4) 4 - ( 27 - 3 ) = x - ( 13 - 4 )
=> 4 - 24 = x - 9
=> 4 - 24 + 9 = x
=> -11 = x
5 ) 13 - ( x- 5 ) = 8
=> x - 5 = 13 - 8
=> x - 5 = 5
=> x = 5 + 5
=> x = 10
\(\left(x-1\right)\left(x-3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-1=0\\x-3=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=1\\x=3\end{cases}}\)
\(\left(x+5\right)\left(x-4\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x+5=0\\x-4=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-5\\x=4\end{cases}}}\)
\(-12+\left(x-9\right)=0\)
\(-12+x-9=0\)
\(-12+x=9\)
\(x=21\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) -5x - (-3) = 13
\(\Rightarrow-5x+3=13\)
\(\Rightarrow-5x=10\)
\(\Rightarrow x=-2\)
Vậy: \(x=-2\)
2) 15 - ( x - 7) = -21
\(\Rightarrow15-x+7=-21\)
\(\Rightarrow15+7-x=-21\)
\(\Rightarrow22-x=-21\)
\(\Rightarrow x=-22-21=-43\)
Vậy: \(x=-43\)
3) 45 - ( x - 9) = -35
\(\Rightarrow45-x+9=-35\)
\(\Rightarrow45+9-x=-35\)
\(\Rightarrow54-x=-35\)
\(\Rightarrow x=-54-35=-89\)
Vậy: \(x=-89\)
4)/x-2/=3\(\Rightarrow\)ta có 2 t/h:
t/h1: x-2=3\(\Rightarrow\)x=2+3=5
t/h2: x-2=-3\(\Rightarrow\)x=2+(-3)=-1
Vậy x=5 hoặc -1
![](https://rs.olm.vn/images/avt/0.png?1311)
dài quá làm hộ câu 1-5 thoy
1) x=21-13
x=8
2)x=-55+41
x=-14
3)x=-21+15
x=-6
4)x=3-3
x=0
5) x= -98-37
x=-135
15 ) 57 - ( x - 46 ) = - 13
57 - x + 46 = -13
103 - x = -13
x = 103 + 13
x = 116
16 ) -x - 23 = -38 - 42
- ( x + 23 )=- ( 38 + 42)
x + 23 = 38 + 42
x = 38 + 42 -23
x = 57
17 ) x - ( - 7 ) = -4 – 14
X + 7 = -18
X = -18-7
X = -25
18 ) 18 - x = -8 - ( - 15 )
18 – x = 7
X = 18 – 7
X = 11
19 ) 45 - ( x + 17 ) = - 26
45 – x - 17 = -26
28 – x = -26
X = 28 + 26
X = 54
20 ) 3. ( x + 5 ) - x - 11 = 24
3x +15 –x – 11 = 24
2x + 4 =24
2x = 24 – 4
2x = 20
X = 20 : 2
X = 10
21 ) 14 - ( x - 7 ) = - 8 - ( - 9 )
14 – x + 7 = 1
21 – x = 1
X = 21 – 1
X = 20
22 ) 15 - ( x - 2 ) = - 7 + 8
15 – x + 2 = 1
17 – x = 1
X = 17 – 1
X = 16
6) x + ( - 71 ) = ( - 55 ) + 85
X – 71 = 30
X = 30 + 71
X = 101
7 ) x - ( - 45 ) = - 63 + 27
X +45 = -16
X = -16 -45
X = - 61